Analysis of the Influence of Digital Technology on the Profitability of KBMI IV Banks In Indonesia - Salsabilla, Andien Febia; Kaluge, David (Contemporary Studies in Economic, Finance and Banking, 2026)
Digital transformation has become a strategic urgency for KBMI IV banks in improving efficiency, competitiveness, and performance stability amid increasingly competitive and technology-based banking industry competition. This study aims to analyze the effect of mobile banking, internet banking, and ATMs on the profitability of KBMI IV banks in Indonesia for the period 2012–2023. The study uses a quantitative approach with the Fixed Effect Model panel data regression method. Profitability is measured using Net Profit Margin (NPM), with control variables in the form of size, Loan to Deposit Ratio (LDR), and BI Rate. The results show that mobile banking and internet banking have a significant positive effect on NPM, while ATMs have no significant effect. The variables of size and BI Rate have a significant positive effect, while LDR is not significant. These findings indicate that digitization can increase profitability when integrated with optimal fund collection and distribution strategies. Therefore, targeted, measurable digital transformation management that is aligned with core banking activities is needed to support long-term performance sustainability.